Strategies for Preventing Civil Servant Turnover: A Case Study of the Ministry of Immigration and Corrections of the Republic of Indonesia - Taufik Hidayat; Hamka Hamka; Ridwan Rajab (Yayasan Riset dan Pengembangan Intelektual, 2026)
Employee turnover is one of the human resource management issues that can affect organizational effectiveness and the sustainability of performance in government institutions. High employee mobility can lead to the loss of potential human resources, decreased productivity, and disruptions in the implementation of organizational tasks. This study aims to analyze the factors causing turnover among civil servants within the Ministry of Immigration and Corrections of the Republic of Indonesia and the strategies for its prevention using the turnover theory proposed by Stephen P. Robbins and Timothy A. Judge, as well as Michael Armstrong’s Strategic Human Resource Management (SHRM) theory. This study employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation and were subsequently analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the factors contributing to employee turnover consist of external factors and labor market conditions at 50%, individual factors and job attitudes at 44.74%, and non-work factors at 5.26%. Based on the theory of Stephen P. Robbins and Timothy A. Judge, these factors are associated with opportunities and/or offers from other institutions, job dissatisfaction due to limited career and competency development, as well as workplace location and family conditions. Meanwhile, Michael Armstrong’s Strategic Human Resource Management perspective highlights the importance of integrating organizational strategies with human resource management practices. The recommended prevention strategies include strengthening career pathways, enhancing competency development, optimizing talent management, and improving job satisfaction in order to increase employee retention.